Persepsi Swamedikasi Berbasis Syariah pada Pasien Geriatri di Apotek Khotidjah - Inesya Febrianing Rizki; Henny Setyo Tur Istanto; Rizky Achmad Faizin (Indonesian Journal of Medical and Pharmaceutical Science, 2026)
Background: Self-medication is the practice of treating common ailments with remedies that can generally be obtained at pharmacies without a doctor's recommendation. While expert guidance is crucial for safe and appropriate self-medication, especially for geriatric patients with declining organ function and degenerative diseases, integrating Islamic values into pharmaceutical services can also influence patient perception. This study aimed to assess the perception of Shariah-based self-medication among geriatric patients at Khotidjah Pharmacy. Methods: This was an observational study using a cross-sectional approach, conducted at Khotidjah Pharmacy from March to April 2024. Data were collected via questionnaires distributed to geriatric patients (aged 45-59) practicing self-medication. A total sampling technique was used, and the questionnaire was validated to have r > 1 and a reliability score of α > 0.831. Results: The study was conducted with 95 respondents. Most had a professional school background (31%) and were self-employed (96%). Regarding customer service perception, in terms of reliability, 100% agreed services were as expected. For responsiveness, 92% agreed employees offered assistance. In assurance, 97% agreed needed medicines were always available. Regarding empathy, 100% agreed employees were ready to help. In tangibility, 98% agreed with neat medicine arrangement. Regarding Shariah-based services, for Rabbaniyyah, 100% agreed the pharmacy encouraged prayer and dhikr. For Akhlaqiyyah, 100% agreed employees greeted patients with "salam" and were friendly and polite. Conclusion: The findings indicate that geriatric patients have a positive perception of Shariah-based self-medication services. Pharmacists at Khotidjah Pharmacy successfully incorporate Islamic values, such as encouraging prayer, greeting with "salam," and providing compassionate and Shariah-compliant services to geriatric patients during self-medication.